Graft-versus-tumor effect of post-transplant cyclophosphamide-based allogeneic hematopoietic cell transplantation - Nakamae, Hirohisa (Frontiers in Immunology, 2024)
Post-transplant cyclophosphamide (PTCy) is becoming the standard prophylaxis for graft-versus-host disease (GVHD) in HLA-haploidentical allogeneic hematopoietic cell transplantation (allo-HCT) and in HLA-matched allo-HCT. Immune reconstitution in the post-transplant setting may influence the graft-versus-tumor (GVT) effect because PTCy has a profound effect on T cell and natural killer cell functions and their reconstitution after allo-HCT. However, many recent studies have shown that the incidence of relapse after allo-HCT with PTCy is comparable to that after conventional allo-HCT. To further improve the outcomes, it is critical to establish a strategy to maintain or effectively induce the GVT effect when using PTCy as a platform for GVHD prophylaxis. However, there is a paucity of studies focusing on the GVT effect in allo-HCT with PTCy. Therefore, focusing on this issue may lead to the establishment of more appropriate strategies to improve transplantation outcomes without exacerbating GVHD, including novel therapies involving cell modification.